2017
DOI: 10.1093/femsyr/fox041
|View full text |Cite
|
Sign up to set email alerts
|

In Saccharomyces cerevisiae gene targeting fidelity depends on a transformation method and proportion of the overall length of the transforming and targeted DNA

Abstract: Gene replacement is one of the most essential approaches in construction of the genetically modified yeast strains. However, the fidelity of gene targeting and the effort needed for construction of a particular strain can vary significantly. We investigated the influence of two important factors-the choice of the transformation method and the design of the transforming DNA fragment, which can vary in overall length (including flanking regions and selectable marker) compared to the length of the targeted region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Unlike the model yeast Saccharomyces cerevisiae , targeted allele replacement in A. fumigatus is complicated by low rates of homologous recombination and the fact that replacement cassettes require long homology arms (LHA) of c. 1 kb ( Stafa et al 2017 ). Improvement in the frequency of homologous recombination can be achieved by employing strains deficient in the non-homologous end-joining (NHEJ) pathway (Δ ku80 , Δ ku70, and Δ lig4 strains) ( da Silva Ferreira et al, 2006 , Ishibashi et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the model yeast Saccharomyces cerevisiae , targeted allele replacement in A. fumigatus is complicated by low rates of homologous recombination and the fact that replacement cassettes require long homology arms (LHA) of c. 1 kb ( Stafa et al 2017 ). Improvement in the frequency of homologous recombination can be achieved by employing strains deficient in the non-homologous end-joining (NHEJ) pathway (Δ ku80 , Δ ku70, and Δ lig4 strains) ( da Silva Ferreira et al, 2006 , Ishibashi et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, frequent TCD in these strains could be a consequence of some mutations, change in gene expression and/or protein activity that remains to be identified. From this point of view, it should be noted that fidelity of gene targeting and spectrum of genetic events strongly depend on the transformation procedure used to deliver the transforming DNA to the yeast cell ( 30 ) as well as on the influence of e.g. EXO1 and SGS1 genes on both transformation efficiency and gene targeting fidelity ( 28 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lithium acetate transformation was done as described previously ( 28 ) but since it was observed that the efficiency of transformation in natural isolates was lower than in commonly used laboratory strains, cells were first allowed to recover for 30 min in rich YPD medium and then plated on selective SC-Ura plates. Isolation of the genomic DNA was performed as described previously ( 29 ) and molecular analysis of transformants was done by Southern blotting ( 30 ) using dioxigenin (DIG)-labelled ADE2 gene (Roche, Darmstadt, Germany). Statistical analysis of the spectra of transformation events was done using two-tailed Pearson’s chi-squared test ( χ 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The transformation of all yeast species in this work was performed using electroporation protocol described in [ 3 ], which was originally developed for transformation of B. bruxellensis. Yeast genomic DNA was isolated as in [ 20 ], and Southern blot was performed as in [ 21 ]. The digoxigenin-labelled probe was synthesized with the DIG DNA Labelling Mix (Roche, Mannheim, Germany), using as a template the PvuII-EcoRI fragment of pRS500 plasmid ( Figure 1 ), thus labelling the gene bla and ori.…”
Section: Methodsmentioning
confidence: 99%